Evaluation of the indoxyl acetate hydrolysis test for rapid differentiation of Campylobacter, Helicobacter, and Wolinella species. - Popovic-Uroic, T (1990)
A total of 410 well-defined Campylobacter, Helicobacter, and Wolinella strains, comprising 26 named species, subspecies, and defined groups, were tested for indoxyl acetate hydrolysis by a disk method by using disks prepared at the Centers for Disease Control, Atlanta, Ga. All C. coli (43 strains), C. cryaerophila (34 strains), C. fennelliae (5 strains), C. fennelliae-Campylobacter-like organism 3 (2 strains), C. jejuni (66 strains), C. jejuni subsp. doylei (3 strains), hippurate-negative C. jejuni-C. coli (15 strains), "C. upsaliensis" (39 strains), H. mustelae (5 strains), W. curva (1 strain), and W. recta (1 strain) hydrolyzed indoxyl acetate. Four strains gave weak positive reactions, and the remaining 196 strains, which belonged to 15 species, subspecies, and defined groups, gave negative reactions. Of the 410 study strains, 246 and 125 strains were tested for indoxyl acetate hydrolysis by a disk method and a tube method, respectively, by using commercially produced disks. The disk method, regardless of source, required less time and interpretation than the tube method did. Better differentiation between Campylobacter spp. was obtained with the indoxyl acetate test than with the trimethylamine N-oxide test. The indoxyl acetate disk distinguished C. lari from C. jejuni and C. coli, C. cinaedi from C. fennelliae, and H. pylori from H. mustelae and suggested that W. succinogenes could be differentiated from W. recta and W. curva. The indoxyl acetate disk method could be performed in 5 to 30 min, was easy to read and interpret, and should be useful as a routine diagnostic test for identification of Campylobacter spp.